Identification of Phenylphthalazinones as a New Class of Leishmania infantum Inhibitors. (9th December 2019) - Sijm, Maarten; de Heuvel, Erik; Matheeussen, An; Caljon, Guy; Maes, Louis; Sterk, Geert‐Jan; de Esch, Iwan J. P.; Leurs, Rob
Abstract: Leishmaniasis is a neglected parasitic disease caused by over 20 different Leishmania species. Current treatments often rely on harsh regimes of pentavalent antimonials such as sodium stibogluconate, while more recent drugs suffer other shortcomings such as low stability and rapid emergence of treatment failure, amongst others. Furthermore, the effectiveness of drugs varies depending on the infecting Leishmania species, thus there is an urgent need for new and effective anti‐leishmanial drugs. Screening of an in‐house compound library identified the hexahydrophthalazinone NPD‐2942 as a low micromolar hit with a pIC50 of 5.8 against L. infantum and a pIC50 of 4.6 for cytotoxicity against human MRC‐5 fibroblasts. To derive structure–activity relationships, we modified the cyclohexyl ring of the hexahydrophthalazinone scaffold and 1, 2, 3‐triazoles were attempted as replacement for the pyrazole ring, amongst others. Ultimately, the 2, 3‐pyrazole‐substituted hexahydrophthalazinone NPD‐1289 was identified as the most potent analogue in this series with a pIC50 of 6.3, although some cytotoxicity toward MRC‐5 cells (pIC50 =5.1) was recorded as well. Replacement of the unsubstituted 2, 3‐pyrazole with 1, 2, 3‐triazoles led to compounds with lower anti‐leishmanial activity. The current scaffold is a valuable new starting point for optimization toward novel anti‐leishmanial drugs. Abstract : Alternative to antimonials : Leishmaniasis is caused by protozoan parasites of the Leishmania family and targets millions of people worldwide. Drugs in current use have several limitations and/or side effects. Therefore, the need for new molecules in the drug discovery pipeline is high. Phenylphthalazinone NPD‐2942 was identified as a hit, and 25 close analogues were prepared to investigate structure‐activity relationships. Several promising analogues were identified which are useful starting points for further optimization.